Syntheses, Structural Characterization, and Kinetic Investigations of Metalla[3]triangulanes: Isoelectronic Nickel(0) and Copper(I) Complexes with Bicyclopropylidene (bcp) and Dicyclopropylacetylene (dcpa) as Ligands. Issue 12 (8th March 2021) - Ritz, Florian J.; Valentin, Lars; Henss, Anja; Würtele, Christian; Walter, Olaf; Kozhushkov, Sergei I.; de Meijere, Armin; Schindler, Siegfried
Abstract: The kinetics of the reactions between [Ni(bipy)(COD)] and bicyclopropylidene (bcp), dicyclopropylacetylene (dcpa) and 1, 4‐dimethoxy‐2‐butyne (dmbu) were investigated using stopped‐flow techniques. Similar to previous studies the results support an associative mechanism (activation parameters for bcp: Δ H # =46±2 kJ ⋅ mol −1 and Δ S # =−69±8 J ⋅ mol −1 ⋅ K −1 ) and therefore allowed to postulate a more general reaction mechanism for the reaction pathway. The products, the nickel(0) complexes [Ni(bipy)(bcp)] and [Ni(bipy)(dcpa)], could be structurally characterized and the molecular structures are presented. In addition, the corresponding copper(I) complexes [Cu(bipy)(bcp)]PF6 and [Cu(bipy)(dcpa)]PF6 were also structurally characterized and their reactivity towards dioxygen was investigated. A detailed discussion of the structural properties and comparisons to similar literature‐known olefinic complexes with transition metals are presented. Abstract : [Ni(bipy)(bcp)], [Ni(bipy)(dcpa)], [Cu(bipy)(bcp)]PF6, and [Cu(bipy)(dcpa)]PF6 (bcp=1, dcpa=2 ) could be structurally characterized and the kinetics of the formation of the nickel complexes from [Ni(bipy)(COD)] were analyzed. A detailed discussion of the structural properties and a comparison to related transition metal complexes are presented.